Analisis Transformasi Digital, Sistem Eletronic Business Terhadap Peningkatan Efisiensi Oprasional Bank Syariah Indonesia - Bengi Asrah; Heny Indriyani; M Dzaky Maulana; Haekal Nafis Ahimsa; Nurbaiti Nurbaiti (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
The study investigates the effects of digital transformation on business electronics on the efficiency of sharia bank operations in Indonesia. Shariah banks in Indonesia are seeking to improve their operational efficiency through investments in digital transformation in the light of rapid technological change. Surveys, interviews, and data analysis from the leading sharia bank in Indonesia are used to conduct research. Studies show that implementing digital transformation into the sharia bank's business electronics system has helped improve operational efficiency, including reducing operating costs, providing better service to customers, and improving accessibility. The study provides important insights for the Indonesian Sharia banking industry on how digital transformation can improve their operational efficiency and provide the basis for further development in this field. presence of additional services